A novel TRPV5/6-like channel from a scleractinian coral - Angélica Méndez-Reséndiz; Gisela E. Rangel-Yescas; Miguel Benítez-Angeles; Tamara Rosenbaum; León D. Islas (PLoS ONE, 2025)
The calcium regulation mechanisms that underlie skeleton formation in stony corals are poorly understood. In epithelial tissues from vertebrates, transient receptor potential vanilloids 5 and 6 (TRPV5 and TRPV6), members of the TRP channel superfamily, play a significant role in transepithelial Ca 2+ transport. Particularly, TRPV5 is a constitutively active channel with a primary function in the Ca 2+ reabsorption mechanism of renal epithelium. It is characterized by a marked inward rectification and a high Ca 2+ permeability at physiological resting membrane potentials. Here, we report the cloning and characterization of a gene that encodes a protein homologous to the inward-rectifier cation channel TRPV5 in the reef-building coral Pocillopora damicornis . We assessed its biophysical properties and found that this channel displays inwardly rectifying Na + currents in the absence of divalent cations and can permeate Ca 2+ , similar to the human TRPV5 channel. When compared to the human TRPV5, the specific blocker of this channel, miconazole, decreased the currents in a dose-dependent manner but did not affect the coral TRPV5/6-like-mediated currents. Interestingly, a monoterpene that has been shown to produce bleaching in corals, is also a blocker of the TRPV5/6-like channel. Altogether, our findings identify for the first time a novel TRPV5/6-like channel in scleractinian corals, whose potential physiological functions may include Ca 2+ transport to support the calcification mechanism.